The statistical analysis of the data of one school SEN pupils - Piaseckienė, Karolina; Ranonienė, Vilma (Lietuvos matematikos rinkinys, 2016)
In the educational process, the special educational needs (for brevity, SEN) are the needs for help and services arising from children’s congenital or acquired disorders and adverse environmental factors. In this article, we analyse statistically the data of pupils with SEN. We create the logistic regression model to describe what determines the proportion of boys among all SEN pupils in certain school.